2002
DOI: 10.1080/14034940210133799
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners' perceived barriers to smoking cessation--results from four Nordic countries

Abstract: The main barriers identified in this study indicate that smoking cessation expertise needs to be more accessible. One alternative is to establish telephone help-lines (Quit-lines) that are easily available for all and could serve as a back-up for the GPs. Another more costly approach is to develop smoking cessation expertise at major clinics. A combination of both is probably the best solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 10 publications
1
44
0
1
Order By: Relevance
“…At present, physician concerns regarding unsolicited smoking cessation advice are well known (Young and Ward 1998, O'Loughlin et al 2001, Helgason and Lund 2002, Bremberg et al 2003, Pilnick and Coleman 2003, Jallinoja et al 2007, and our research findings and those of other qualitative studies of smokers' receptivity to such advice suggest that these concerns are well founded. This marked disjuncture between qualitative research findings regarding the acceptability of physician smoking cessation advice and the systematic reviews of quantitative studies regarding its effectiveness speaks to some of the limitations of EBM as an effective tool for guiding individual clinical practice.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…At present, physician concerns regarding unsolicited smoking cessation advice are well known (Young and Ward 1998, O'Loughlin et al 2001, Helgason and Lund 2002, Bremberg et al 2003, Pilnick and Coleman 2003, Jallinoja et al 2007, and our research findings and those of other qualitative studies of smokers' receptivity to such advice suggest that these concerns are well founded. This marked disjuncture between qualitative research findings regarding the acceptability of physician smoking cessation advice and the systematic reviews of quantitative studies regarding its effectiveness speaks to some of the limitations of EBM as an effective tool for guiding individual clinical practice.…”
Section: Discussionsupporting
confidence: 49%
“…2 GPs cite fear of harming the doctor-patient relationship as a frequent barrier to discussing smoking with patients , Bremberg et al 2003, Pilnick and Coleman 2006. Other physician-identified barriers to greater involvement in this work include: patients' perceived unwillingness to change, time constraints, perceived ineffectiveness of interventions, lack of confidence or expertise, lack of financial incentive and a lack of supportive resources (O'Loughlin et al 2001, Young and Ward 2001, Helgason and Lund 2002, Coleman et al 2004, Vogt et al 2005, Twardella and Brenner 2005, Boldemann et al 2006, Coleman et al 2007, Jallinoja et al 2007.…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies assessed GP's attitudes without assessing whether the GPs actually perform the behavior later on or whether they actually provide smoking counseling [1,7,13,17].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies confirm these obstacles along with lack of knowledge, poor confidence in skills, and inadequate institutional or clinic support (Gottlieb et al, 2001;Pollak et al, 2001;Suchanek Hudmon et al, 2003). Helgason and Lund (2002) found that a shortage of smoking cessation experts to whom physicians could refer their patients was the most common barrier in smoking cessation. Our study findings indicated the FMRs' solution to the barriers was to refer to the NP where they had confidence in the care of their patient.…”
Section: Discussionmentioning
confidence: 91%